In vivo evaluation of different formulation strategies for sustained release injectables of a poorly soluble HIV protease inhibitor - Muees, Joke; Scurr, David J.; Amssoms, Katie; Annaert, Pieter; Davies, Martyn C.; Roberts, Clive J.; Mooter, Guy Van den (Elsevier, 2015)
At present no scientific rationale exists for selecting a particular enabling strategy to formulate a poorly water-soluble drug, although this is crucial as it will influence the in vivo performance of the resulting formulation. This study provides an insight into this complicated decision making process for a poorly soluble human immunodeficiency virus (HIV) protease inhibitor based upon in vivo test results. A formulation strategy based on the molecular dispersion of this active pharmaceutical ingredient (API) into a biphasic matrix consisting of water-insoluble poly(lactic-co-glycolic acid) (PLGA) and water-soluble polyvinylpyrrolidone (PVP) was evaluated. The long-term in vivo performance of this strategy was compared to that of other solubility enhancing approaches by evaluating the exposure in male Beagle dogs. Solid dispersions, based on a PLGA/PVP matrix, were compared to solid dispersions in a pure water-insoluble PLGA matrix. Additionally these solid dispersion strategies were compared to the strategy of particle size reduction by means of an API microsuspension. The in vivo performance of the various formulations over a period of 28 days after intramuscular injection was evaluated by the observed initial burst release, plasma concentration-time profiles, time at which maximum plasma levels were reached (tmax,obs) and the estimated bioavailability. Compared to the other formulation strategies assessed, it was concluded that the addition of PVP in a PLGA matrix resulted in vivo in a more sustained release as well as a higher amount of drug released from the polymeric matrix. This was explained based on the structure of these binary PLGA/PVP matrices where the pore network originating from rapidly dissolving PVP plays a crucial role. Moreover, the results suggest that the release of this type of formulations could be delayed by increasing the amount of PLGA in the formulation.